Do the Indicators of Entrepreneurial Ecosystem Show Signs Of Improvement In India, Pakistan, And Bangladesh? Dynamic And Static Comparative Studies Among the Three Entrepreneurial Ecosystems in The Indian Subcontinent - Nandy, Subhashis (European Scientific Journal, ESJ, 2020)
Research studies in the past have enunciated the status of the entrepreneurial ecosystem (EE) in India (Nandy 2018), Pakistan (Asif and Ellahi, 2016), and Bangladesh (Cho, Sultan, and Kwon, 2019). However, no study so far has focused on comparison of the dynamic (longitudinal) and the static (cross-sectional) aspects of the EE of these three countries. This paper focuses on the dynamic and static comparisons of the indicators of EE in India, Bangladesh, and Pakistan, based on the most recent survey data available from Global Entrepreneurship Monitor and World Bank. The results of this analysis show that all three countries in the Indian subcontinent have made some improvements in 2020 in most of the indicators of entrepreneurial ecosystem. Further, the results of the non-parametric hypothesis test indicate that the scores of these three countries are significantly different from that of the world’s first-ranked country - New Zealand in 2020.